(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Arterial hypertension (AH) is one of the most common chronic diseases, closely associated with the risk of developing various vascular disorders, including retinal damage. One of the key pathophysiological mechanisms underlying these conditions is endothelial dysfunction, which plays a crucial role in vascular permeability, blood flow regulation, and the activation of inflammatory processes. Endothelial dysfunction contributes to the progression of both arterial hypertension and retinal pathologies, such as hypertensive retinopathy, necessitating a comprehensive approach to diagnosis and correction.